Semiotic Analysis Of Peace In Salaamun Alaikum By Anis Syusyan According To Michael Riffatere Theory - As'ad, Jinani Firdausi; Sabiila, Diyanah Hanin (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2024)
The poem